Upaya Pembinaan Keimanan Siswa di MI Mujahidin Kecamatan Sooko Kabupaten Mojokerto - Robi'in, Muhammad; Akbar, Aziz (Adabuna : Jurnal Pemikiran dan Pendidikan, 2022)
Faith development efforts are a process of maturing students in order to understand the teachings of Islam and at the same time be applied in everyday life. In faith development efforts there are several components that support each other, namely: (1) Objectives, (2) Materials, (3) Methods and approaches, (4) Facilities and infrastructure, and (5) Evaluation. MI Mujahidin in Sooko District, Mojokerto District with its faith development efforts can create high quality human resources in terms of science, faith and piety. Through fostering faith in the aspects of aqidah, worship and morals, it is hoped that after students grow up, their faith will remain embedded in their souls. With the selection of appropriate methods and approaches, the goals set at MI Mujahidin Sooko District Mojokerto Regency can be achieved.This study aims to determine: (1) Efforts to foster faith in the students of MI Mujahidin in Sooko District, Mojokerto Regency (2) Efforts to foster faith applied to the students of MI Mujahidin in Sooko District, Mojokerto Regency. This study uses the method of field research (field research) with description analysis techniques. The collected research data was analyzed using deductive and inductive approach. The results show that efforts to foster faith in students at Mujahidin have been planned and programmed.